Empowerment of Farmers Through the Online Extension in Improving Agricultural Information Literacy - Whisnu Febry Afrianto; Susanti Indriya Wati; Rivandi Pranandita Putra; Taufiq Hidayatullah (Universitas Mataram, 2022)
The COVID-19 pandemic has impacted all countries around the world, including Indonesia. The COVID-19 pandemic affects all sectors, especially the agrocomplex. As a strategic step to minimize the impact on the agricultural sector, it is necessary to have a digital transformation to support production stability. Digital media in agriculture can be used as a medium for consulting farmers with agricultural experts so there is validation of information obtained by farmers regarding problems in the field. This empowerment activity was conducted to increase the literacy skills of farmers on cultivation topics as a supporting system for food security during the COVID-19 pandemic. Klinik tanipanen was created to provide a medium for farmers to consult directly with agricultural experts. The topic problems are about cultivation techniques (upstream and farming), agroindustry, and marketing. Based on the activities that have been carried out, the majority of farmers' questions are about pests and diseases encountered in the field. Through this program, it is expected that farmers will be able to improve their literacy skills, thereby increasing their productivity and income.